Understanding writing strategy use from a sociocultural perspective: The case of skilled and less skilled writers. (August 2016) - Lei, Xiao
Abstract: Research on writers' strategy use has proliferated over the past four decades. However, few studies have specifically compared skilled and less skilled student writers' strategic use of mediating resources in spite of the recent popularity of including sociocultural perspectives in L2 writing research. Drawing on the activity theory and the concept of internalisation, this study examines four skilled and four less skilled student writers' mediation strategy use. Data were collected from multiple sources, including interviews, process logs, stimulated recalls and students' essays. Data analysis revealed that although the two groups of students tend to use similar types of resources, internalisation of them differs significantly. Differences are mainly found in three sub-processes of internalisation, namely, noticing, imitating and goal setting. The identified importance of these sub-processes to internalisation suggests that language learners should raise their language awareness, make persistent imitations and integrate learning-to-write with writing-to-learn for more effective strategy use.